CHEMICAL CHARACTERISTICS AND NUTRITIVE QUALITY OF NOVEL FUNCTIONAL POTATO CHIPS-LIKE PRODUCTS - naeem, rehab (Food and Feed Research, 2024)
DevelopinDeveloping countries, including Egypt, are suffering from serious nutritional problems among school-aged children and adolescents as they consume snacks and fast food, leading to serious health problems. Therefore, the production of affordable potato chips-like products containing functional ingredients such as sesame seeds and flaxseeds is one of the best ways to deal with such problems. This study found that these ingredients provided several macronutrients to the consumers in the following ranges: 9.62% - 12.88% of crude proteins, 5.23% - 13.73% of crude fat, 2.09% - 5.19% of crude fibres and 7.17% - 8.43% of ash which indicates the presence of important minerals such as phosphorus, calcium, iron, magnesium, manganese, and zinc. Potato chips-like snack that contained whole ground sesame seeds (15%) and flaxseeds (15%), was the highest in minerals except for potassium and sodium, and it was the only sample to contain a small amount of selenium. In addition, it contained the highest amount of omega-3 fatty acids followed by that enriched with 15% partially defatted sesame seeds and 15% whole ground flaxseeds. On the other hand, the potato chips-like snacks enriched with 15% of partially defatted sesame seed and flaxseeds each, and that enriched with 15% whole ground sesame seeds and 15% partially defatted flaxseeds, were more stable in oxidative stability than the previous two potato chips-like snacks. Also, the potato chips-like snacks enriched whole sesame and flax seeds as well as that with partially defatted sesame seeds and whole ground flaxseeds exerted the highest antioxidant activity confirmed by the DPPH scavenging and the number of phenolic compounds. The microstructure of the particles in the samples determined by scanning electron microscopy (SEM) showed that the chips-like snack with partiall defatted sesame and flaxseeds was the best sample in terms of particle structure and distribution compared to the rest of the samples. Finally, the sensory properties of the potato chips-like snacks with defatted sesame and flaxseeds and a combination of wholeground sesame seeds/defatted flaxseeds were scored higher for overall acceptability and other sensory attributes.